2019
DOI: 10.21580/jiafr.2019.1.1.3745
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regional original income and balance funding on regional government financial performance

Abstract: <p class="IABSSS"><strong>Purpose</strong> - The purpose of the research was to determine the effect of local revenue and intergovernmental revenue on the financial performance of local government.</p><p class="IABSSS"><strong>Method </strong>- This research used Stewardship Theory. The method used is quantitative research method. The method of data analysis used is multiple linear regression analysis. This research used secondary data. The population in this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
2
14
0
5
Order By: Relevance
“…The results of this study support Budi's research (2017), Siswadi (2015) and Awwaliyah, Agriyanto & Farida (2019) which states that the General Allocation Fund negatively and significantly affects the Human Development Index. High General Allocation Fund allocation with a basic allocation component is still the main component that dominates the overall General Allocation Fund received by the district.…”
Section: The Effect Of General Allocation Fund On Human Development Isupporting
confidence: 88%
“…The results of this study support Budi's research (2017), Siswadi (2015) and Awwaliyah, Agriyanto & Farida (2019) which states that the General Allocation Fund negatively and significantly affects the Human Development Index. High General Allocation Fund allocation with a basic allocation component is still the main component that dominates the overall General Allocation Fund received by the district.…”
Section: The Effect Of General Allocation Fund On Human Development Isupporting
confidence: 88%
“…In the context of the agency theory, the people act as the principal by providing funding for local retributions, and the local government acts as the agent, who executes responsibility in managing its funds, which originate from the people, to drive other activities in order to achieve the goal of the organization. Andrei 2013, Aswar (2019) and Awwaliyah et al (2019) found that local own-source revenue positively significant on the local governments financial performance. Therefore, the hypothesis formulated: H2: Local Own-Source Revenue positively significant on the Local Governments Financial Performance.…”
Section: The Effect Of Local Own-source Revenue Towards Local Governmmentioning
confidence: 99%
“…The central government acts as the principal in relation to the agency theory, and local g and the local government acts as the agent, in which the central government delegates authority to the local government in managing the finances from received funds, and the local government must assume responsibility on behalf of that authority by managing finances well, an also optimally and fairly increase the quality of public services. This will improve the local government's financial efficiency, based on studies conducted by Andirfa et al (2016) and Awwaliyah et al (2019), which show that fiscal balance transfer has a positive effect on the financial performance of local governments. The hypothesis is formulated on the basis of the explanation above: H1: Fiscal Balance Transfer positively significant on the Local Governments Financial Performance.…”
Section: Hypothesis and Conceptual Frameworkmentioning
confidence: 99%
“…Tax planning organizes individual taxpayers and enterprise entities by utilizing various possibilities of loopholes taken by companies in the corridor of tax regulations so that taxpayers can pay a minimum amount (Pohan, 2013). This study's measurement of tax planning is calculated through tax retention rate, which analyzes the effectiveness of tax management in financial reporting for the current year (Awwaliyah et al, 2019). The calculation of the effectiveness of tax management itself is the calculation of the effectiveness of tax planning (Aditama & Purwaningsih, 2014).…”
Section: Tax Planningmentioning
confidence: 99%